2019
DOI: 10.1038/s41598-019-47872-4
|View full text |Cite
|
Sign up to set email alerts
|

Kefir peptides alleviate particulate matter <4 μm (PM4.0)-induced pulmonary inflammation by inhibiting the NF-κB pathway using luciferase transgenic mice

Abstract: Kefir peptides, generated by kefir grain fermentation of milk proteins, showed positive antioxidant effects, lowered blood pressure and modulated the immune response. In this study, kefir peptide was evaluated regarding their anti-inflammatory effects on particulate matter <4 μm (PM 4.0 )-induced lung inflammation in NF-κB-luciferase +/+ transgenic mice. The lungs of mice under 20 mg/kg or 10 mg/kg PM 4.0 treatments, both increased significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
2
16
0
Order By: Relevance
“…The kefir-fermented product derived from a milk protein source used in this study to determine the potential role of KPs in the management of salt-induced chronic kidney disease contained 15.48 g/100 g peptide, and its main components are listed in Supplementary Table S1 . The reproducibility of the prepared kefir peptides was high, as shown in our previous study [ 16 , 19 , 20 ].…”
Section: Methodssupporting
confidence: 58%
See 1 more Smart Citation
“…The kefir-fermented product derived from a milk protein source used in this study to determine the potential role of KPs in the management of salt-induced chronic kidney disease contained 15.48 g/100 g peptide, and its main components are listed in Supplementary Table S1 . The reproducibility of the prepared kefir peptides was high, as shown in our previous study [ 16 , 19 , 20 ].…”
Section: Methodssupporting
confidence: 58%
“…After sacrificing the rats, the upper lateral half of the kidney tissue was freshly dissected. These tissues were fixed in 10% buffered formaldehyde (pH 7.0), embedded in paraffin, sectioned into 3 μm sections, and processed for three types of histopathological stains: hematoxylin and eosin (H&E) [ 19 ], Masson’s trichrome [ 20 ] and Sirius red [ 25 ]. The severity of the observed lesions was graded by a pathologist according to the standard method [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many of these byproducts may have extensive outcomes in the host without the presence of a microbial community [ 48 ]. Chen et al studied the anti-inflammatory and antioxidant activities of kefir peptides against particulate material smaller than 4 μm (PM 4.0 )-induced lung inflammation in transgenic homozygous nuclear factor-kappa B (NF-κB)-luciferase +/+ mice [ 27 ]. They demonstrated that kefir peptides had potent anti-inflammatory effects through reduction of expression of the proinflammatory cytokines IL-lβ, IL-4, IL-6 and TNF-α in lung tissue by inhibition of NF-κB signalling.…”
Section: Characterisation and Potential Use Of Kefirmentioning
confidence: 99%
“…Kefir has been shown to inhibit angiotensin-converting enzyme (ACE) levels, cholesterol metabolism, accelerate wound healing, suppress tumour growth, and cause alterations in the immune system to improve asthma symptoms and allergy [ [22] , [23] , [24] , [25] ]. Kefir and kefir derivatives (e.g., polysaccharides, protein, peptides) can suppress viral activity by modulating immune-system responses and/or causing disruption of viral adhesion [ 26 , 27 ]. They also act as anti-inflammatory agents by inhibiting the activity of proinflammatory cytokines such as IL-1β, tumour necrosis factor (TNF)-α and IL-6 [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation